1975
DOI: 10.2135/cropsci1975.0011183x001500010004x
|View full text |Cite
|
Sign up to set email alerts
|

Solute Loss from Deteriorated Cottonseed: Relationship Between Deterioration, Seed Moisture, and Solute Loss1

Abstract: Loss of electrolytes from cottonseed (Gossypium hirsutum L.) soaked in water was influenced by factors in the processing history of the seeds, such as delinting procedure and post‐delinting washing. Measurements of electrolyte loss were most reproducible if they determined a change during an interval (15 to 45 min) not inclusive of zero time. Cottonseed (G. hirsutum ‘Deltapine 16’) that deteriorated under controlled conditions of 100% relative humidity and 35 to 50 C was reduced in viability and exhibited incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
14

Year Published

1984
1984
2004
2004

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 0 publications
1
7
0
14
Order By: Relevance
“…In addition, it focus on a specific ion, while the electrical conductivity test evaluates a set of electrolytes release (Panobianco & Marcos-Filho, 2001a). Simon & Raja-Harun (1972) and Halloin (1975) determined the leakage intensity during imbibition of pea and cotton seeds, respectively, and verified a strong relation between the results of the electrical conductivity test and the amount of potassium leached by seeds. Woodstock et al (1985) concluded that the potassium and calcium leakage from cotton seeds were promising as assessment indexes of seed physiological potential, emphasizing that potassium leachate results were more consistent than those of the electrical conductivity test.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…In addition, it focus on a specific ion, while the electrical conductivity test evaluates a set of electrolytes release (Panobianco & Marcos-Filho, 2001a). Simon & Raja-Harun (1972) and Halloin (1975) determined the leakage intensity during imbibition of pea and cotton seeds, respectively, and verified a strong relation between the results of the electrical conductivity test and the amount of potassium leached by seeds. Woodstock et al (1985) concluded that the potassium and calcium leakage from cotton seeds were promising as assessment indexes of seed physiological potential, emphasizing that potassium leachate results were more consistent than those of the electrical conductivity test.…”
Section: Introductionmentioning
confidence: 70%
“…Potassium has been shown to be the main ion leached by seeds during imbibition, followed by sodium and calcium, and may be used as an indicator of cell membrane integrity (Halloin, 1975). The potassium leachate test is based on the same principle of the electrical conductivity test with the additional advantage of producing results in a considerable shorter period of time.…”
Section: Introductionmentioning
confidence: 99%
“…Conforme trabalhos realizados por Halloin (1975), McKersie & Stinson (1980) e Woodstock et al (1985, a quantidade de K liberado por sementes embebidas tem sido utilizada como indicador da integridade do sistema de membranas celulares.…”
Section: Resultsunclassified
“…Constata-se, ainda, com relação a este fungo, maior ocorrência do mesmo nas sementes deslintadas tratadas com o PCNB+extrato e extrato de aroeira puro. Provavelmente, essa ocorrência e a ação patogênica deste fungo, tenham levado à redução da germinação e do vigor das sementes analisadas em ambas as cultivares que receberam estes tratamentos, o que está de acordo com Halloin (1975), quando salienta que, sementes de algodoeiro infectadas com esta espécie fúngica têm sua qualidade fisiológica reduzida mais rapidamente do que outras espécies. Quanto ao Fusarium sp, comparando-se as cultivares (Tabela 5), não foram constatadas diferenças significativas; também, não foram verificadas diferenças entre todos os tratamentos utilizados nas sementes da cv.…”
Section: Resultsunclassified
“…Precoce 2, pelo PCNB+extrato. Para as sementes com línter (Tabela 6), a incidência desse fungo contribuiu para a redução da viabilidade e do vigor das mesmas, concordando dessa forma com Halloin (1975) e Lima et al (1984), ao comentarem que o Rhizopus, quando inoculado em sementes do algodoeiro, afeta de imediato o vigor, estando provavelmente associado ao apodrecimento da semente durante o início do processo de germinação. Nas sementes tratadas com o extrato de aroeira puro, as incidências de todos os fungos foram superiores aos demais tratamentos, exceto para o Aspergillus sp.…”
Section: Resultsunclassified